Biodegradable polymers and platelet-rich plasma causing visual impairment: a literature review - Lee, Kar Wai Alvin; Chan, Lisa Kwin Wah; Lee, Angela Wai Kay; Lee, Cheuk Hung; Wan, Jovian; Yi, Kyu-Ho (The Journal of dermatological treatment, 2024)
Dermal fillers are widely used for facial rejuvenation and esthetic enhancement, offering temporary solutions for aging and volume loss. Despite their general safety, a rare but severe complication associated with these fillers is visual impairment, including blindness. This underscores the need for a thorough understanding of risks associated with various filler materials. Historical cases of blindness following filler injections date back to 1963, with increasing reports linked to the expansion of the cosmetic filler industry. While hyaluronic acid (HA) and autologous fat have been extensively studied, other fillers such as calcium hydroxylapatite and poly-l-lactic acid (PLLA) are less understood. This systematic review aims to address gaps in the literature by providing a comprehensive overview of visual impairment caused by fillers other than HA and autologous fat. We systematically examine the prevalence, causes, clinical features, and treatment outcomes associated with these less common fillers. A comprehensive literature search was conducted across databases including PubMed, Scopus, and Google Scholar using terms related to visual impairment and dermal fillers. Studies published between 2014 and 2021, including observational studies and case reports, were included. Studies were selected based on predefined inclusion and exclusion criteria, and a PRISMA flow diagram was used to illustrate the study selection process. The review identifies and summarizes cases of visual impairment associated with calcium hydroxylapatite, poly-d,l-lactic acid (PDLLA), and PLLA fillers. Key findings reveal that visual impairment following these fillers is rare but can occur suddenly or within a few days of the procedure. Cases of delayed onset up to two weeks are also noted, emphasizing the need for extended post-procedure monitoring. The review highlights unique insights into the risks associated with non-HA fillers, such as the heightened risk in the periorbital region and other facial areas. It explores mechanisms of complications, including retrograde flow of emboli leading to retinal ischemia. The discussion also covers emergency protocols and preventative measures, providing valuable guidance for managing and mitigating risks. Visual impairment caused by fillers other than HA and autologous fat, while rare, represents a serious complication that requires careful attention. This review contributes new perspectives on the differential risks of various fillers, symptom onset variability, and anatomical risk factors. Emphasizing the importance of proper patient selection, technique, and monitoring, it calls for further research to better understand and prevent these complications, ultimately aiming for safer and more effective use of soft-tissue fillers.